Sustainability versus fishing collapse: a review of causes and welfare prescriptions - Peña, Julio (Estudios de Economía, 2016)
It is commonly held that fishing collapse is a public bad. Losses in genetic endowment and the closure of fishing industries underlie this concern. This paper discusses both the welfare functional as well as the technological factors that condition this belief. Fishing collapse is analysed as an opportunity cost within society’s investment decision in other available, natural and man-made, assets. We also review and analyse conditions traditionally associated with the occurrence of fishing collapse. We discuss different causality links between these conditions and collapse, for different types of fishery settings. This analysis helps us to differentiate between superficial and more fundamental causes of collapse. Priorities in regulation policy can the be obtained.